Different methods of managing bluestem pasture - Smith, E.F.; Anderson, K.L.; DeGeer, C.V. (Kansas Agricultural Experiment Station, 2011)
This experiment was to determine the effect of different stocking rates, of deferred grazing, and of pasture burning on cattle performance, productivity of pastures, and range condition as determined by plant population changes. In addition to the yearly report, a summary of cattle gains for the past 16 years is included.
Keywords: Beef; Bluestem pasture; Stocking rates; Pasture burning; Performance